(3GdfgGjI TQM GdgOGjIs - (3GdMSjf Hf Ydj Hf MLGL Hf Ydj, MSGe GdOjf GdpqSrZnfGbj , J (B711 (3g` s; (3GdeQZjfGfj , Ydj Hf CHj HcQ Hf YHO GdLdjd GdaQZGfj GdeQZjfGfj, HQgGf GdOjf CHh GdMSf,J (B593 (3g` s
(3ChdgG (B:s
(3cJGH GdEbGdI s
(3BNQgG (B:s
(3BNQ cJGH GdgHI hGdUObI s
(3fSNI QGHYIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B266 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B45s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B9 - (3U (B275 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B2032s
Keywords: (3Gdabg GdMfajs